Quality counts - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Persuading buyers that they are buying a better product than is on offer anywhere else is one of the keys to successful marketing. The special processing of a product often provides that key. In Comoros, for example, vanilla is subjected to a...